The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1016/0163-7258(81)90097-8
|View full text |Cite
|
Sign up to set email alerts
|

History of pharmacokinetics

Abstract: of absorption at time t, V is the volume of distribution, C is the plasma drug concentration at time t and k is the first-order elimination rate constant. In 1937, Teorell, a Swedish physiologist and biophysicist, published two remarkable articles which many now attribute as being the foundations of modern pharmacokinetics (Teorell, 1937a,b). The model of Teorell was one of the first physiologically-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(43 citation statements)
references
References 208 publications
0
42
0
1
Order By: Relevance
“…PK studies in animals were routinely used by drug discovery projects before the development and validation of predictive in vitro tools. It is possible that the use of PK studies today is influenced by that legacy, and strategies have not fully evolved to reflect the power of predictive tools currently available [1,2].Although the fundamentals of what we would now recognize as pharmacokinetic theory and analysis were established by 1960 [3], it took another 20 years before PK studies started to become integral to the drug discovery process [4]. There were four keys steps that made PK optimization an achievable medicinal chemistry goal, thrusting drug metabolism and pharmacokinetics to the heart of discovery projects.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…PK studies in animals were routinely used by drug discovery projects before the development and validation of predictive in vitro tools. It is possible that the use of PK studies today is influenced by that legacy, and strategies have not fully evolved to reflect the power of predictive tools currently available [1,2].Although the fundamentals of what we would now recognize as pharmacokinetic theory and analysis were established by 1960 [3], it took another 20 years before PK studies started to become integral to the drug discovery process [4]. There were four keys steps that made PK optimization an achievable medicinal chemistry goal, thrusting drug metabolism and pharmacokinetics to the heart of discovery projects.…”
mentioning
confidence: 97%
“…Although the fundamentals of what we would now recognize as pharmacokinetic theory and analysis were established by 1960 [3], it took another 20 years before PK studies started to become integral to the drug discovery process [4]. There were four keys steps that made PK optimization an achievable medicinal chemistry goal, thrusting drug metabolism and pharmacokinetics to the heart of discovery projects.…”
mentioning
confidence: 99%
“…As reviewed by Wagner,22) and Rowland and Tozer, 23) pharmacokinetics is a kinetic method advanced from classical kinetic theory applied to study drugs and toxins, and is useful for diagnosis and therapeutic treatments. In pharmacokinetics, the kinetic processes of the drug in the body are simply divided into five steps referred to as ADME, that is, absorption (A), distribution (D), metabolism (M) and excretion (E), and assumed usually to be a linear first-order reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, no one has examined absolute calcium bioavailability using modern pharmacokinetics, even though Yergey et al 19) indicated theoretically that the fractional absorption using dual-isotope approaches are closely related to the concept of absolute bioavailability defined from pharmacokinetics. 22,23) To examine different calcium supplements, the absorbability of various calcium salts has been studied, and results indicated that food or its elements, like lactose, can enhance calcium absorption via a paracellular route in the intestine, [26][27][28] but what causes the different degrees of absorption between the calcium salts is a topic of discussion. Several studies have suggested that solubility plays a crucial role in intestinal absorption, [29][30][31] but others have suggested that solubility has little or no correlation with bioavailability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation